Major dietary patterns in relation to disease severity, symptoms, and inflammatory markers in patients recovered from COVID-19 - Ebrahimzadeh, Armin; Taghizadeh, Mohsen; Milajerdi, Alireza (Frontiers in Nutrition, 2022)
Background COVID-19 is a highly transmissible viral infection with high morbidity. Few studies have been done about dietary intakes in patients with COVID-19. This study aimed to evaluate the association between major dietary patterns before COVID-19 diagnosis in recovered patients and the risk of disease severity and symptoms after the disease begins. Methods Overall, 250 recovered cases with both genders completed study questionnaires providing data on demographic characteristics, self-reported web-based 168-item food frequency questionnaire (FFQ), and COVID-19 outcomes in Shahid Beheshti Hospital, Kashan. PCR was used to determine a positive diagnosis of COVID-19. We used multivariable logistic regression models to assess the association between major dietary patterns and study outcomes. All statistical analyses were done by SPSS version 16. Results We identified three major dietary patterns—unhealthy, traditional, and healthy dietary patterns. Serum levels of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were significantly higher in patients with unhealthy and traditional dietary patterns and lower in those with healthy dietary patterns. There was a significant direct relationship between unhealthy and traditional patterns with risk of severe COVID-19 and hospitalization duration and a significant direct association between an unhealthy pattern and the odds ratio (OR) of convalescence duration. A significant inverse relationship was found between healthy pattern and risk of severe COVID-19 and OR of convalescence duration. We found a significant direct association between unhealthy pattern and OR of cough, fever, chilling, weakness, myalgia, nausea and vomiting, and sore throat and between traditional pattern and OR of cough, fever, and chilling. In contrast, a significant inverse association was seen between healthy pattern and OR of dyspnea, weakness, and sore throat. Conclusion This study showed that high adherence to an healthy pattern was associated with lower CRP and ESR levels and lower risk of severe COVID-19, hospitalization, and convalescence duration in patients who recovered from COVID-19. More adherence to unhealthy or traditional dietary patterns was associated with higher CRP and ESR levels and a higher risk of severe COVID-19 and hospitalization duration. A direct association was found between unhealthy and traditional patterns and the risk of some COVID-19 symptoms, while an inverse association was found for a healthy dietary pattern.